Technological Integration and Human Resource Psychology: Examining the Interrelationship and Its Implications in the Digital Workplace - Khan, Zafar; Amin, Muhammad Akbar; Talha; Ahmad, Ghayur (The Indonesian Institute of Science and Technology Research, 2025)
The convergence of psychological principles and technological advancements reshapes how organizations manage human resources (HR). As emerging technologies like artificial intelligence (AI), automation, and digital platforms permeate the workplace, they significantly influence employee behavior, motivation, satisfaction, and performance. This study explores the complex relationship between technology and HR from a psychological perspective. Using a qualitative meta-analysis and case-driven synthesis, we identify key psychological outcomes associated with technology integration and assess their implications for organizational development. The findings indicate that while facilitating operational efficiency, technology also contributes to challenges related to mental workload, technostress, digital competency gaps, and organizational alienation. Moreover, employee engagement, trust, adaptability, and psychological safety become critical in maximizing the benefits of tech-driven HR systems. This paper contributes to understanding how to harmonize technological innovation with psychological well-being in HR practices, offering insights for scholars and practitioners.